Utility of Aprepitant in the Management of Pediatric Patients with Cyclical Vomiting Syndrome: A Comprehensive Review - Hayder Yousef Ahmad Alqanber et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Cyclical Vomiting Syndrome (CVS) is a challenging pediatric disorder characterized by recurrent episodes of intense nausea and vomiting, significantly impacting the quality of life and healthcare utilization. Despite its unclear etiology, treatment primarily aims to manage acute episodes and prevent recurrence. Aprepitant, a neurokinin-1 (NK1) receptor antagonist originally developed for chemotherapy-induced nausea and vomiting (CINV), has emerged as a promising therapeutic option in CVS management. This review examines the current evidence on the utility of aprepitant in pediatric CVS, exploring its mechanism, clinical efficacy, safety profile, and potential limitations. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/288 DOI: https://doi.org/10.5281/zenodo.14541589